Detection of Bla CTX-M gene on Resistant Salmonella enterica serovar from a Hospital in Southeast Nigeria - O.E., Adeleke,; N.E., Onyenwe,; T.I., Mbata, (Asian Journal of Biological and Life Sciences, 2012)
Typhoid fever appears to be a disease that has been associated with man since close to the first appearance of hominids. A total of twenty-five clinical isolates of Salmonella enterica serovars recovered between July-September, 2011 were investigated and screened using molecular methods for the presence of bla CTX-M type gene and plasmids. Polymerase Chain Reaction analysis showed that the four of the S.enterica encoding the CTX-M type gene CTX-M were mostly Extended Spectrum β-Lactamase producers which had no plasmids DNA. Phenotypic analysis reveals that the enzymes were active on Ceftazidime (64%) more than Cefotaxime(16%). Two folds serial dilution method reveals that Cefotaxime had increased Minimum Inhibitory Concentration (MIC) ranging from 1.56ug/ml- 12.5ug/ml depending on the isolates and the β-lactamase enzyme produced. The four blaCTX-M gene detected on the adult Patients were from the General Out Patients Department(GOPD) and National Health Insurance Scheme(NHIS) section of the hospital in Eastern Nigeria.